(±)-5-Ethyl-2-(4-isopropyl-4-methyl-5-oxo-4,5-dihydro-1H-imidazol-2-yl)nicotinic acid - Dai, Wei (International Union of Crystallography, 2008)
In the title compound, C(15)H(19)N(3)O(3), owing to an intramolecular O—H⋯N hydrogen bond, the pyridine and imidazole rings are nearly coplanar and are twisted from each other by a dihedral angle of only 0.92 (9)°. The molecules are linked through intermolecular N—H⋯O hydrogen bonding, forming an infinite chain parallel to the b axis.